2022
DOI: 10.1101/2022.08.22.504704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-associated reduction of nuclear shape dynamics in excitatory neurons of the visual cortex

Abstract: External stimuli contribute to the neuronal properties partly through regulating gene expression. Previous works have shown nuclear infolding induced by external stimuli and pathological conditions in neurons. However, the dynamics and reversibility of the changes in nuclear shape upon external stimuli have been unknown. In this study, we found that the nuclear shape of excitatory neurons in the visual cortex altered and undergo invagination upon visual stimuli. Subsequently, we performed time-lapse imaging of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…These results also indicate that neuronal activity induced by external stimuli alters nuclear morphology, which may be crucial for regulating gene expression and chromatin structure. It has also been reported that this nuclear infolding is a reversible process [27]. In nuclei of young neurons, morphological changes of the nuclear periphery were observed within 10 minutes after stimulation, and the nuclei returned to a spherical shape when the stimulus was removed, whereas, in nuclei of aged neurons, the dynamic behavior of the nuclei was reduced.…”
Section: Neuronal Senescencementioning
confidence: 87%
“…These results also indicate that neuronal activity induced by external stimuli alters nuclear morphology, which may be crucial for regulating gene expression and chromatin structure. It has also been reported that this nuclear infolding is a reversible process [27]. In nuclei of young neurons, morphological changes of the nuclear periphery were observed within 10 minutes after stimulation, and the nuclei returned to a spherical shape when the stimulus was removed, whereas, in nuclei of aged neurons, the dynamic behavior of the nuclei was reduced.…”
Section: Neuronal Senescencementioning
confidence: 87%